Extending the window for thrombolysis for treatment of acute ischaemic stroke during pregnancy: a review. (29th September 2020) - Dinehart, E; Leon Guerrero, C; Pham, A; Chandra, S; Petersen, SM; Bathgate, S; Ahmadzia, H
Abstract : Historically, safety of intravenous recombinant tissue plasminogen activator (IV rt‐PA) for the treatment of acute ischaemic stroke (AIS) is limited to use within 4.5 hours from symptom onset. Recent studies suggest the treatment window may be extended when patients have salvageable brain tissue on advanced neuroimaging. This paper describes a novel use of IV rt‐PA for treatment of AIS in a pregnant patient within an extended‐time window (>4.5 hours, and <9 hours) based on advanced neuroimaging with a favourable outcome. Tweetable abstract: Novel use of IV rt‐PA for treatment of AIS in pregnancy within an extended‐time window based on advanced imaging with a favourable outcome. Tweetable abstract: Novel use of IV rt‐PA for treatment of AIS in pregnancy within an extended‐time window based on advanced imaging with a favourable outcome.